Transforming human capital for the digital age: industry 4.0 and 5.0 - Rasha Aldrickzler; Mudhafar Yaseen Saadoon; Raad Tomaa Kawad; Ivan Chornomordenko (Encuentros)
The advent of Industry 4.0 and 5.0, characterized by integrating modern technologies and automation, significantly reshapes the workplace and the need for specific skills. The article aims to analyze the impact of Industry 4.0 and 5.0 on human resources, focusing on the challenges and benefits these technological breakthroughs provide for workforce expansion. This study investigates the impact of Industry 4.0 and 5.0 on human capital via a comprehensive analysis of current trends and future projections. The article suggests that Industry 4.0 and 5.0 provide significant challenges to the labor market, including job displacement and the need for skill adaption. Nevertheless, they also provide significant potential for enhancing productivity and competitiveness. The report emphasizes the immediate need for focused investment in enhancing human resources, facilitated by advantageous governmental policies and educational overhauls.